Aplikasi Media Pembelajaran Kimia untuk SMA Kelas X - David Gunawan; Kristo Radion Purba; Silvia Rostianingsih (Jurnal Infra, 2016)
Student often have problems when learning science because some theory unobserveable at daily life. As an example, it is hard to imagine that coffee powder does not really combined with water particle. For those reason, simulation techonology has been created.Learning media which created in this thesis based on looped animation and interactive system that purposed on assisting student to learn chemist in interactive module. Application designed for four chemist lesson which implemented in simulation, several quiz and games. Mixture lesson displayed in interactive simulation that student can try some simple experiment. Atom’s model, Periodic Table and Chemical bond displayed in interactive media that encourage student to explore the content of lesson themselves.Test result shown that the application is able to help student to learn chemist theory. Three part of application give adequate lesson for student and a part of application need more improvement. Animation used in application is able to improve student’s understanding about chemist theory.